Salivary sex hormones & its relation to periodontal status among pregnant & non pregnant women (Mustansiria Dental Journal, 2018)
Salivary sex hormones (estradiol/ progesterone) levels may rise dramatically &may affect the periodontal health during pregnancy. The aim of this study was tomeasure the level of estradiol &progesterone in stimulated saliva of pregnant women& its correlation to periodontal status in comparison to non pregnant women.A total of 26 women of the age group 20-24yr. attending the maternal & childhealth care in the medical city hospital were selected at the 3rd trimester of pregnancy& another 26 unmarried women were selected rand only. Saliva had been collectedfor analysis of estradiol & progesterone & periodontal status had been evaluated usingplaque index (PlI), gingival index (GI), probing depth (PD) & clinical attachmentlevel (CAL), t-test, X2 & correlation coefficient were used where indicated.The results revealed a significant difference in the mean PlI & GI among pregnant& control groups. Pregnant women showed deeper pocket & more attachment loss &a high mean of salivary sex hormones than control group with significant differences.The results also revealed a positive correlations between probing depth, clinicalattachment level & salivary sex hormones while there was no significant weakcorrelation between PlI, GI with salivary sex hormones.All the periodontal parameter & salivary sex hormones in this study were highervalue in pregnant women than non pregnant with significant differences. More strongpositive correlations were found between PD, CAL with salivary sex hormones &weak correlations with PlI & GI.